Macroeconomic Variable and It's Influence On Performance of Indonesian Islamic Banking - Yoghi Citra Pratama (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
The  purpose  of  this  research  is  to  analyze  the macroeconomics  variables  that  affect  to  the  performance  of  Islamic  banks  in Indonesia. Methods used in this research is the Vector Auto regressive (VAR) / Vector Error correction model (VECM) to see the effect of the shock and the long-term effect on the performance of Islamic Banking. The results show that based on the analysis of IRF, the performance of Islamic banking having short-term shocks to fluctuations in macroeconomics variables but stable in the long term, and based on the variance decomposition, shocks of macro variables only gives little effect on the performance of Islamic banking.DOI:10.15408/aiq.v7i1.1359